Produção de audiovisuais no processo de ensino-aprendizagem: uma proposta avaliativa - Rezende, Eduardo Vieira de (2014)
This work aims the development an evaluative proposal pointing criteria that may be used by teachers in the production of an audiovisual physics program that approach key contents for the understanding of various natural phenomena processes. The audiovisual production efficiency by high school students was already proved in the literature, however, in most of the times, teachers without a starting point aren't able to evalute because both how to and evaluating criteria aren't well defined. In methodological terms, students were encouraged to develop an entire script recording from theme to completion and the film editing as well. At this point, the teacher uses an interdisciplinary work with writing teachers, regarding to the linguistic aspects of the script. Concept, specific physics, and language, referring to structural issues of language: criteria linked to the review of the script, which was divided into two great moments were presented. We have observed that the students' audiovisual production is a way to motivate the research, the work group and the immersion in a meaningful school environment. The results obtained in this study has allowed the development of criteria that will be used to evaluate the efficiency of an audiovisual production by high school students. We conclude that the criteria used to assess these audiovisual projects were satisfactory, ranging from the development of scripts to the final production post on youtube. In this work, the assistent teacher can lead students to implement instructions in their classrooms. Furthermore, we've also developed an evaluative proposal which points different criteria that could be used to assess these audiovisual produced. It's important to say that each criterion was evaluated under teacher's responsability. Finally, the results of this dissertation has pointed to ways to evaluate audiovisual projects and incorporate more criteria to them.